2009
DOI: 10.1348/026151008x345591
|View full text |Cite
|
Sign up to set email alerts
|

Associations between parental control and children's overt and relational aggression

Abstract: The present study examined specialized associations between parental control and child aggression in a sample of 600 8- to 10-years old children. Parental control dimensions and aggression subtypes were assessed using multiple informants (i.e. children, mothers, fathers, peers, and teachers). In line with expectations, parental physical punishment was positively associated with overt aggression, whereas parental psychological control was positively associated with relational aggression in both girls and boys. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
48
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 56 publications
2
48
0
Order By: Relevance
“…The extent that fathers uniquely engaged in psychological control, relative to mothers, was also predictive of girls' relational aggression. Research with a Belgian middle-childhood sample has also shown, for both mothers and fathers, that psychological control is predictive of relational aggression and physical punishment is predictive of physical aggression (Kuppens et al 2008).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The extent that fathers uniquely engaged in psychological control, relative to mothers, was also predictive of girls' relational aggression. Research with a Belgian middle-childhood sample has also shown, for both mothers and fathers, that psychological control is predictive of relational aggression and physical punishment is predictive of physical aggression (Kuppens et al 2008).…”
Section: Discussionmentioning
confidence: 97%
“…The studies that do exist suggest that both negative (e.g., corporal punishment, psychological control) and positive (e.g., warm and responsive) forms of parenting are concurrently associated with more or less relational aggression in preschoolers (Brown et al 2007;Casas et al 2006;Hart et al 1998;Nelson et al 2006), children in middle childhood (Kuppens et al 2008;Nelson and Crick 2002), and adolescents (Loukas et al 2005). These studies predominantly emphasize a social-learning perspective, in which the nature of the parent-child relationship serves as the prototype of basic relationship functioning.…”
Section: Parenting Practices and Children's Hostile Behavior And Intementioning
confidence: 99%
“…A number of studies confirm that parental psychological control is related to children's relational aggression, even in non-Western cultures (e.g., Casas et al, 2006;Kuppens, Grietens, Onghena, & Michiels, 2009;Loukas, Paulos, & Robinson, 2005;Nelson & Crick, 2002;Nelson, Hart, Yang, Olsen, & Jin, 2006). However, both physical and relational aggression are usually associated with both spanking and psychological control, so the theoretical specificity (suggested above) is lacking (cf., Kuppens et al, 2009).…”
mentioning
confidence: 99%
“…However, both physical and relational aggression are usually associated with both spanking and psychological control, so the theoretical specificity (suggested above) is lacking (cf., Kuppens et al, 2009). The gist is that aversive parenting models aggressive behavior more generally.…”
mentioning
confidence: 99%
See 1 more Smart Citation